2019
DOI: 10.1016/j.jctube.2019.100121
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life with tuberculosis

Abstract: Tuberculosis diagnosis and treatment currently revolves around clinical features and microbiology. The disease however adversely affects patients’ psychological, economic, and social well-being as well, and therefore our focus also additionally needs to shift towards quality of life (QOL). The disease influences all QOL domains and substantially adds to patient morbidity, and these complex and multidimensional interactions pose challenges in accurately quantifying impairment in QOL. For this review, PubMed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 85 publications
2
59
0
13
Order By: Relevance
“…This may have resulted in de novo HPV infections and re-infections. This scenario is supported by the latest evaluations of the positive effects of TB treatment on the physical, emotional and psychological health of TB patients [ 105 ]. Thus, sociodemographic features of WLWH with TB, suggested an explanation for the increased prevalence of HR HPVs in those receiving ART and ART/TB-treatments in their improved health allowing return to everyday life with capacity to work and upkeep sexual relations.…”
Section: Discussionmentioning
confidence: 77%
“…This may have resulted in de novo HPV infections and re-infections. This scenario is supported by the latest evaluations of the positive effects of TB treatment on the physical, emotional and psychological health of TB patients [ 105 ]. Thus, sociodemographic features of WLWH with TB, suggested an explanation for the increased prevalence of HR HPVs in those receiving ART and ART/TB-treatments in their improved health allowing return to everyday life with capacity to work and upkeep sexual relations.…”
Section: Discussionmentioning
confidence: 77%
“…The results also indicated that tuberculosis -from the most to the least-mostly affects the physical, functional/independence, and social/family domains of QoL. Prolonged cough, fever, weakness and fatigue, chest pain, and weight loss are among the most common physical problems caused by TB (2), which in turn reduce the patient's ability and physical function and pave the way for the emergence of social and family problems (30).…”
Section: Discussionmentioning
confidence: 99%
“…Saat ini layanan pengendalian TB terfokus terhadap penyembuhan terhadap mikrobiologisnya, sedangkan pasien TB juga mengalami penderitaan secara mental dan sosial. 13 Program kuratif sendiri dirasa memakan biaya cukup tinggi sehingga dilakukannya manajemen kesehatan dengan tatalaksana komprehensif diantaranya adalah promotif, preventif, kuratif, dan rehabilitatif dirasa lebih efektif. 14 Promosi kesehatan adalah kegiatan penyuluhan dengan tujuan memastikan perilaku dan kesejahteraan hidup manusia.…”
Section: Pendahuluanunclassified